2015
DOI: 10.1186/s12866-015-0412-x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble factors from biofilms of wound pathogens modulate human bone marrow-derived stromal cell differentiation, migration, angiogenesis, and cytokine secretion

Abstract: BackgroundChronic, non-healing wounds are often characterized by the persistence of bacteria within biofilms - aggregations of cells encased within a self-produced polysaccharide matrix. Biofilm bacteria exhibit unique characteristics from planktonic, or culture-grown, bacterial phenotype, including diminished responses to antimicrobial therapy and persistence against host immune responses. Mesenchymal stromal cells (MSCs) are host cells characterized by their multifunctional ability to undergo differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 53 publications
4
59
0
Order By: Relevance
“…Exposure to biofilm-conditioned media as well as isolated soluble biofilm factors alone are both sufficient to impair MSC migration and differentiation while promoting apoptosis. 53 These findings suggest that chronic wounds provide a suboptimal environment for transplanted stem cells, which may thus impede the utility of stem cell therapy in chronic wounds, at least in those with ongoing bacterial colonization with biofilm forming organisms.…”
Section: Infectionmentioning
confidence: 94%
“…Exposure to biofilm-conditioned media as well as isolated soluble biofilm factors alone are both sufficient to impair MSC migration and differentiation while promoting apoptosis. 53 These findings suggest that chronic wounds provide a suboptimal environment for transplanted stem cells, which may thus impede the utility of stem cell therapy in chronic wounds, at least in those with ongoing bacterial colonization with biofilm forming organisms.…”
Section: Infectionmentioning
confidence: 94%
“…This corroborates the finding in several in vitro studies that have shown that the presence of infection reduces, but does not completely inhibit, the differentiation of MSCs, likely through the effects of soluble factors secreted by the S. aureus biofilm. 17,18 Main effect analysis for BMP-5 expression indicates that infection is an independent negative factor in the production of BMP-5, suggesting that prophylactic treatment with clindamycin could be beneficial from the perspective of infection treatment and restoration of growth factor expression. In addition, clindamycin treated defects, with or without infection, also retain similar VEGF expression to the material control, further demonstrating that defects treated at the time of initial surgery are able to maintain the ability to generate membranes with appropriate growth factor expression.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Staphylococcus aureus is the most common infecting agent in long bone osteomyelitis and is known to have deleterious effects on local cell populations. [16][17][18] In vitro studies have shown the effects of S. aureus on local cells to be far reaching, such as decreasing osteoblast viability and differentiation, inhibiting the multilineage potential of mesenchymal stem cells (MSCs), increasing the production of resorptive factors and increasing the production of proinflammatory cytokines. [17][18][19] These effects are not conducive to the regeneration of bone, and thus, local antibiotic delivery is intended to eradicate bacteria to restore the regenerative capacity of local cell types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been discovered to possess tissue replacement and wound healing properties, mainly due to their differentiation ability to many cell types [1,[14][15][16][17][18]. As recent studies demonstrated, stem cells have migrated towards the microenvironments which are infected by H. pylori [1,6]; the main factors for attracting MSCs are chemotaxi cytokines that are particularly released in the chronic infection specially H. pylori infections [1,19]. Stem cells have more abilities than other cells to temporarily put off and control the cells' normal growth and start extra proliferation for their innate duty in ulcer and wound healing [20,21].…”
Section: Introductionsmentioning
confidence: 99%